Response of internal solitary waves to tropical storm Washi in the northwestern South China Sea - Z. H. Xu; Z. H. Xu; B. S. Yin; B. S. Yin; Y. J. Hou; Y. J. Hou (Annales Geophysicae, 2011)
Based on in-situ time series data from an array of temperature sensors and an acoustic Doppler current profiler on the continental shelf of the northwestern South China Sea, a sequence of internal solitary waves (ISWs) were observed during the passage of tropical storm Washi in the summer of 2005, which provided a unique opportunity to investigate the ISW response to the tropical cyclone. The passing tropical storm is found to play an important role in affecting the stratification structure of the water column, and consequently leading to significant variability in the propagating features of the ISWs, such as the polarity reversal and amplitude variations of the waves. The response of the ISWs to Washi can be divided into two stages, direct forcing by the strong wind (during the arrival of Washi) and remote forcing via the near-inertial internal waves induced by the tropical storm (after the passage of Washi). The field observations as well as a theoretical analysis suggest that the variations of the ISWs closely coincide with the changing stratification structure and shear currents in accompanied by the typhoon wind and near-inertial waves. This study presents the first observations and analysis of the ISW response to the tropical cyclone in the South China Sea.